Financial viability of inserting the biofloc technology in a marine shrimp Litopenaeus vannamei farm: a case study in the state of Pernambuco, Brazil - Soares Rego, Marcelo Augusto; Sabbag, Omar Jorge [UNESP]; Soares, Roberta; Peixoto, Silvio (Springer, 2017)
This study analyzed the financial viability of inserting the biofloc technology (BFT) system and maintaining the conventional culture system for the marine shrimp Litopenaeus vannamei in a farm located in the state of Pernambuco, northeastern Brazil. To obtain information related to investment and operating costs, we used three ponds (625 m(2) each) covered with high-density polyethylene operating with the BFT system and data from three conventional ponds (2.86 ha each) used in a farm during 2014. The total production costs of BFT were eight times higher than the conventional system. Operating profit and profitability index were US$ 51,871.54 ha(-1) year(-1) and 30.22 % for BFT, and US$ 21,523.83 ha(-1) year(-1) and 59.79 % for the conventional system, respectively. In investment analysis, indicators were favorable for both systems, with greater expressiveness of the net present value (NPV) for the BFT (US$ 142,004.42) and internal rate of return (IRR) 4.5 times higher for conventional system (131.86 %). To achieve favorable results of profitability and viability, combined with the ability to contribute to the sustainable development of marine shrimp farming, the BFT system is a promising alternative to replace traditional systems used in northeastern Brazil.
Keywords: Biofloc; Costs; Internal rate of return; Net present value; Profitability; Sensitivity; Shrimp farming